CGIAR Initiative on One Health: Annual Technical Report 2022 - CGIAR Initiative on One Health (CGIAR System Organization, 2023)
CGIAR Technical Reporting has been developed in alignment with the CGIAR Technical Reporting Arrangement. This Initiative report is a Type 1 report and constitutes part of the broader CGIAR Technical Report. Each CGIAR Initiative submits an annual Type 1 report, which provides assurance on Initiative-level progress towards end-of-Initiative outcomes. The CGIAR Technical Report comprises (i) the Type 1 Initiative and Impact Area Platform reports, with quality assured results reported by Initiatives and Platforms available on the CGIAR Results Dashboard; (ii) the Type 3 Portfolio Performance and Project Coordination Practice Change report, which focuses on internal practice change; and (iii) the Portfolio Narrative, which draws on the Type 1 and Type 3 reports, and the CGIAR Results Dashboard, to provide a broader view on portfolio coherence, including results, partnerships, country and regional engagement, and synergies among the portfolio’s constituent parts. The CGIAR Technical Report constitutes a key component of the CGIAR Annual Performance Report.